2013
DOI: 10.3390/agriculture3020271
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Greenhouse Gas Emissions Associated with Worm Control in Lambs

Abstract: There are currently little or no data on the role of endemic disease control in reducing greenhouse gas (GHG) emissions from livestock. In the present study, we have used an Intergovernmental Panel on Climate Change (IPCC)-compliant model to calculate GHG emissions from naturally grazing lambs under four different anthelmintic drug treatment regimes over a 5-year study period. Treatments were either "monthly" (NST), "strategic" (SPT), "targeted" (TST) or based on "clinical signs" (MT). Commercial sheep farming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 20 publications
(36 reference statements)
0
17
0
1
Order By: Relevance
“…However, a recent study of 131 beef and 57 sheep farms in England by the English Beef and Lamb Executive (EBLEX, 2012) suggested that low carbon farms generally were those that achieve optimum daily live-weight gains and finish as early as possible. A recent UK study, demonstrated that effective management of gastrointestinal parasites can reduce a farm's GHG budget under simulated commercial farming conditions (Kenyon et al, 2013). Further data on commercial farms are required to expand the evidence base and it is possible that further production data from our study will give insight into the impact of sustainable control strategies on potential emissions under different weather patterns.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, a recent study of 131 beef and 57 sheep farms in England by the English Beef and Lamb Executive (EBLEX, 2012) suggested that low carbon farms generally were those that achieve optimum daily live-weight gains and finish as early as possible. A recent UK study, demonstrated that effective management of gastrointestinal parasites can reduce a farm's GHG budget under simulated commercial farming conditions (Kenyon et al, 2013). Further data on commercial farms are required to expand the evidence base and it is possible that further production data from our study will give insight into the impact of sustainable control strategies on potential emissions under different weather patterns.…”
Section: Discussionmentioning
confidence: 92%
“…Parasitic diseases are a major constraint to optimum livestock production and are the major cause of economic loss in UK sheep flocks with farmers remaining dependant on anthelmintics for control. It has been suggested that animals may emit higher levels of greenhouse gases if growth and production are affected by sub-clinical illness (Gill et al, 2009) and so the development of sustainable strategies that lower methane emissions may contribute significantly to reducing a farm's environmental footprint (Kenyon et al, 2013). With increasing reports of anthelmintic resistance worldwide (dos Santos et al, 2014;Geurden et al, 2014;Karrow et al, 2014), control strategies for gastrointestinal nematodes that minimise the use of anthelmintics are of increasing importance.…”
Section: Introductionmentioning
confidence: 98%
“…Liver fluke in cattle, for instance, is estimated to increase greenhouse gas emissions per affected cow by 10% . Anthelmintic control strategies have been shown to reduce farm-level greenhouse gas emissions (Kenyon et al, 2013). The effect of helminth control on water use remains to be assessed but is likely to be beneficial, given increased thirst in animals affected by protein-losing gastro-enteritis.…”
Section: Future Considerations For Integrated Decision-makingmentioning
confidence: 99%
“…Liver fluke in cattle is estimated to increase greenhouse gas emissions per affected cow by 10% (Elliott et al, 2014;Williams et al, 2015). Kenyon et al (2013) investigated different anthelmintic strategies in sheep and concluded that effective management of gastrointestinal parasites can reduce farm--level greenhouse gas emissions. To the authors' knowledge however, no data on poultry parasites are available.…”
Section: Applying the Framework To Coccidiosis In Broilersmentioning
confidence: 99%